Transnational parenthood and forced migration: the case of asylum-seeking parents who are forcibly separated from their families by immigration laws - Madziva, Roda (Policy Press, 2015)
Within transnational studies literature, there is a tendency to assume that migrant parents have ready access to paid work once they arrive in countries of destination, which subsequently enables them to maintain transnational ties with children and kin left behind. In this article I argue that more attention needs to be paid to the ways in which immigration regimes and policies construct certain groups of migrants, such as asylum-seekers, as underserving of the rights to sell their labour and the adverse consequences these often have on parents’ identities and transnational capabilities. The argument builds on the case study of a group of Zimbabwean asylum-seeking parents. Like many asylum-seekers escaping politically repressive regimes, they had not managed to bring their children with them when they escaped to the UK, but had imagined that, once in a ‘safe haven’, they would be able to arrange for their children to join them. On arrival, they discovered that the UK immigration system treats parents as asylum-seekers first and parents later (if ever). This article furthers understanding of transnational parenting from the perspectives of a migrant group for whom labour market demand is not the sole objective for its mobility.